End-of-Life Product Recovery Chain Planning and Future Research Needs - Mohamad-Ali, Nurhasyimah; Ghazilla, Raja Ariffin Raja; Abdul-Rash, Salwa Hanim; Sakundarini, Novita; Ahmad-Yazid, Aznijar; Stephenie, Lydyaty (International Journal of Engineering and Technology, 2018)
Nowadays, there is a significant increase in the productivity of the automotive industry with a variety of vehicle types and models being produced constantly. This in turn, leads to problems with end-of-life vehicle (ELV) management. Even though ELV management occurs at the end of the vehicle life cycle, the design stage plays a pivotal role to ensure the effectiveness of ELV management. Although the relevant parties involved strive to manage and improve ELV recovery by careful design planning using various modelling tools, there are still several issues that need to be addressed such as development of a reliable recovery infrastructure, implementation of ELV recovery policies as well as extended producer responsibility issues. In addition, there is a need for information sharing and collaboration from all stakeholders in the ELV recovery chain due to the fact that many factors are interrelated and subjected to dynamic changes. For this reason, predicting how end-of-life (EOL) strategies affects the effectiveness of ELV recovery is an arduous task, particularly in an export-dependent nation such as Malaysia. In this study, we propose a model that offers a more holistic view of ELV recovery in Malaysia using the system dynamics approach. Our model is developed based on the current scenario of the automotive industry in Malaysia. We believe that our model will facilitate product designers in incorporating EOL strategies during the early stages of product design and development.